Caesarean sections and private insurance: systematic review and meta-analysis - Ilir Hoxha; Medina Braha; Lamprini Syrogiannouli; David C Goodman; Peter Jüni; Bruno R da Costa (BMJ Open)
Objective Financial incentives associated with private insurance may encourage healthcare providers to perform more caesarean sections. We therefore sought to determine the association of private insurance and odds of caesarean section.Design Systematic review and meta-analysis.Data sources MEDLINE, Embase and The Cochrane Library from the first year of records through August 2016.Eligibility criteria We included studies that reported data to allow the calculation of OR of caesarean section of privately insured as compared with publicly insured women.Outcomes The prespecified primary outcome was the adjusted OR of births delivered by caesarean section of women covered with private insurance as compared with women covered with public insurance. The prespecified secondary outcome was the crude OR of births delivered by caesarean section of women covered with private insurance as compared with women covered with public insurance.Results Eighteen articles describing 21 separate studies in 12.9 million women were included in this study. In a meta-analysis of 13 studies, the adjusted odds of delivery by caesarean section was 1.13 higher among privately insured women as compared with women with public insurance coverage (95% CI 1.07 to 1.18) with no relevant heterogeneity between studies (τ2=0.006). The meta-analysis of crude estimates from 12 studies revealed a somewhat more pronounced association (pooled OR 1.35, 95% CI 1.27 to 1.44) with no relevant heterogeneity between studies (τ2=0.011).Conclusions Caesarean sections are more likely to be performed in privately insured women as compared with women using public health insurance coverage. Although this effect is small on average and variable in its magnitude, it is present in all analyses we performed.